Effects of compressive force, particle size and moisture content on mechanical properties of biomass pellets from grasses - Mani, Sudhagar; Tabil, Lope G.; Sokhansanj, Shahab (Biomass & bioenergy, 2006)
Mechanical properties of wheat straw, barley straw, corn stover and switchgrass were determined at different compressive forces, particle sizes and moisture contents. Ground biomass samples were compressed with five levels of compressive forces (1000, 2000, 3000, 4000 and 4400 N) and three levels of particle sizes (3.2, 1.6 and 0.8 mm) at two levels of moisture contents (12% and 15% (wet basis)) to establish compression and relaxation data. Compressed sample dimensions and mass were measured to calculate pellet density. Corn stover produced the highest pellet density at low pressure during compression. Compressive force, particle size and moisture content significantly affected the pellet density of barley straw, corn stover and switchgrass. However, different particle sizes of wheat straw did not produce any significant difference on pellet density. The relaxation data were analyzed to determine the asymptotic modulus of biomass pellets. Barley straw had the highest asymptotic modulus among all biomass indicating that pellets made from barley straw were more rigid than those of other pellets. Asymptotic modulus increased linearly with an increase in compressive pressure. A simple linear model was developed to relate asymptotic modulus and maximum compressive pressure.